Politics, Policy and Public Administration in Theory and Practice - de Percy, Michael; Podger, Andrew; Vincent, Sam; de Percy, Michael; Podger, Andrew; Vincent, Sam (Canberra ANU Press, 2021)
This festschrift celebrates the extensive contribution John Wanna has made to the research and practice of politics, policy and public administration. It includes both personal acknowledgements of his work and substantial essays on the issues that he focused most closely upon during his academic career: budgeting and financial management, politics, and public policy and administration. The essays address contemporary developments in public sector financial management in Australia and overseas, changing political processes in Queensland and the Commonwealth, and public governance and administration reform trajectories in Australia and internationally, including in China. A common theme is the importance of linking research to practice, reflecting John Wanna's own style and contribution. Essays include exploration of the interface between academia and practice, including from the perspective of practitioners. The authors of the essays in this volume include eminent Australian and international scholars of public administration, experienced public service practitioners and younger scholars influenced by John Wanna.
English
Keywords: Political science & theory; Public administration; Central government policies; Regional government policies; John Wanna; public administration; politics; public policy